Importance measures in reliability, risk, and optimization : principles and applications - Kuo, Way, 1951- (Wiley, 2012)
"Provides a comprehensive introduction to importance measures in reliability and optimization, allowing readers to address real, large-scale problems within various fields effectivelyThe book is divided into five main parts, the first containing background information on the fundamentals of system reliability. The second part introduces importance measures, including: the Birnbaum importance measure; the Barlow-Proschan importance measure; the Fussell-Vesely importance measure; and the Natvig time-dependent lifetime importance measure. This part also covers structure importance measures, importance measures of pairs of components, and generalizations of importance measures. Part three looks at applications. Importance measures in redundancy allocation and fault diagnosis are discussed, along with importance measures in upgrading systems and in operations research. The fourth part covers comparisons of importance measures and importance measures for con/k/n systems. The final part to the book discusses components assignment problems (CAP), including sections on CAP in coherent systems, CAP in con/k/n/ and its variant systems, and heuristics based on the Birnbaum reliability importance for CAP. A full appendix contains acronyms and notation, errors and ambiguities found in the literature. First book to systematically interpret various importance measures in the field of reliability engineering, to investigate the precise relationships among various importance measures, and to present their applications in the areas of reliability, operations research, and optimization Includes extensive coverage, from the early study of reliability importance to the state-of-the-art in network analysis, multistate systems, and applications in modern systems Contains many case studies, examples, illustrations and tables"--